Comparison of the Antioxidant Activity of Traditional Herbal Loloh from Bali as an Immunity Booster - Ni Putu Widayanti; Ayu Saka Laksmita W.; Desak Putu Risky Vidika Apriyanthi; Ni Made Widnyani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Loloh is a local wisdom product of the Balinese people that has been passed down from generation to generation, processed from plant leaves. Consumption of loloh is utilized by the community as a preventive measure to prevent disease and increase body immunity. This has great potential to be applied in facing the growing disease trends in the future, starting from infectious diseases and non-infectious diseases (degenerative). Herbal drinks in general made from ginger, turmeric and temulawak have been widely studied. However, until now, the antioxidant power of loloh from Bali is not yet known. The purpose of this study was to determine the comparison of the antioxidant power of traditional Balinese loloh.This study used a descriptive explorative and experimental design by applying the DPPH (2,2-diphenyl-1-picrylhydrazyl) method to determine the antioxidant power of each loloh sample by looking at its IC50 value. The data collection technique uses purposive sampling. The number of samples studied in this study was ten samples including loloh cemcem, beras kencur, rosella, telang, mengkudu, kelor, kunyit asam, temu kunyit, kunyit asam sirih, and cincau hijau. Data analysis was conducted using regression equations. The results of IC50 measurements showed that the traditional loloh that had very strong antioxidant activity was loloh kelor leaves with an IC50 value of 98 ppm, weak antioxidant activity was possessed by loloh rosella flower tea and cincau leaves with IC50 values of 168 ppm and 198 ppm while very weak antioxidants were possessed by loloh telang flowers, cemcem, beras kencur, mengkudu, kunyit asam, temu kunyit, and kunyit asam sirih with IC50 values > 200 ppm.